Roll on Columbia [videorecording (VHS)] : Woody Guthrie & the Bonneville Power Administration - Majdic, Michael; Matthews, Denise (Knight Library Media Services, University of Oregon, 1999)
In 1941, Woody Guthrie and his family left southern California for a job in Portland, Oregon writing songs for a documentary film about the dams being built on the Columbia River. The story is told through interviews with family and friends; and archival footage that includes scenes from both Hydro and The Columbia, documentaries made by the BPA's public information department in the late '30s and '40s.